Case Report: Campylobacter fetus caused pyogenic spondylodiscitis with a presentation of cauda equina syndrome after instrumented lumbar fusion surgery - Topolovec, Matevž; Faganeli, Nataša; Brumat, Peter (Frontiers in Surgery, 2022)
Spondylodiscitis with/without neurologic impairment is a serious infection, predominantly occurring in high-risk patients. Campylobacter Fetus caused spondylodiscitis is very rare. Evidence-based therapeutic concepts for lumbar spondylodiscitis are lacking. A 64-year-old high-risk woman underwent decompression with instrumented lumbar fusion. Six months after index surgery she developed pyelonephritis, which deteriorated to sepsis and presentation of cauda equina syndrome. She underwent urgent revision with decompression, debridement and instrumentation removal, and received long-term antibiotics. Culture grew Campylobacter Fetus, previously not reported as a cause of spondylodiscitis after elective instrumented lumbar fusion. Emergent debridement and removal of instrumentation, with two months of targeted intravenous antibiotics followed by six weeks of oral antibiotics led to complete spondylodiscitis resolution. Prompt diagnostics and targeted antibiotic treatment are paramount when dealing with spinal infections, particularly in patients with rare causative pathogens like Campylobacter Fetus. Concomitant neurological complications may require emergent surgical management in the case of cauda equina syndrome.